Performance Model of Vaname Shrimp Farmer Group in Muaragembong District, Bekasi Regency - Setiawan, Rully; Nidar, Sulaeman Rahman; Sutisna, Sutisna (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aimed to investigate the impact of empowerment, competence, and transformational leadership on performance, as well as the effect of these factors on the welfare of vaname shrimp farmers in Muaragembong District, Bekasi Regency. The research used descriptive and verification methods, employing path analysis to analyze the data. The respondents were members of Pokdakan Mina Bakti, with interviews and questionnaires used to measure the influence of each variable. The results indicated that empowerment and leadership had no significant impact on performance, while competence had a positive effect on member performance. Empowerment and competence were found to have a positive impact on the welfare of the members, along with performance. However, leadership had a negative effect on welfare. The study also established a model showing that members played a crucial role in improving welfare, emphasizing the importance of training programs and motivation from the head of the farm. Training activities should focus on the development of techniques and addressing modern farming challenges to enhance shrimp productivity and quality. Finally, the provision of supportive facilities and infrastructure was recommended to further support the members.